Racial and gender income inequality in the American states - Critzer, John W (Race and Society, 1998)
The purpose of this article is to uncover the political factors associated with greater income parity for black men, black women, and white women relative to white men in the American states. Variables are constructed for federal, state, and local government employment, state electoral competition, federal procurement, black state legislators, and women state legislators along with a number of socioeconomic factors. It is discovered that the political variables carry less weight than the socioeconomic ones. These findings raise questions about the future prospects for increased earnings parity for minorities and women as previous federal efforts to eliminate racial and gender discrimination appear to have been weakened and state political factors have little relationship with greater income equality.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-943-206-707-051 tex.type: [object Object]
Keywords: dept.psc

Book Reviews - Critzer, John W. (The American Review of Public Administration, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1995RY11400008 tex.unique-id: [object Object]
Keywords: book.review; dept.psc

Blacks and women in public higher education: Political and socioeconomic factors underlying diversity at the state level - Critzer, John W.; Rai, Kul B. (Women & Politics, 1998)
In this paper, we analyze the political and socioeconomic factors that may be associated with black and female employment in American public higher education. We develop representation ratios for black females, black males, white females, and white males who serve as full-time faculty members in public higher education institutions in the American states. Our analysis shows that region, in this case the South, provides the best indicator for black female and black male faculty employment in public higher education. The percentage of black state legislators is also associated with black faculty employment. For white women, we found that although they are well represented on faculties, their numbers do not reach their share of the population. None of the variables examined explained their employment as faculty members. Women as a group had a particularly weak presence in state legislatures and continue to have less political power than blacks and white males. We suggest a number of possible avenues for future research to clarify these findings.
_eprint: https://doi.org/10.1300/J014v19n01_02 tex.ids: ISI:000073528000002 tex.organization: Int Polit Sci Assoc tex.unique-id: ISI:000073528000002
Keywords: dept.psc; ⚠️ Invalid DOI